2013
DOI: 10.1017/s0960258512000281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on the cell cycle of germinating maize seeds (Zea maysL.)

Abstract: During seed germination, metabolism is reactivated, DNA is repaired and cell division is restarted in the meristems. The mechanisms that co-ordinate cell growth and division in maize embryonic axes during germination are not well understood. However, the presence of a factor similar to IGF (insulin-like growth factor) that accelerates germination has been reported. In the present work, the regulation of the cell-cycle restart by bovine insulin [which has been demonstrated to produce similar effects as insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(80 reference statements)
3
6
0
Order By: Relevance
“…Previous results from our research group have already proven that cell division in calli tissues occurs by stimulation with ZmIGF or insulin, 39 and recent evidence also showed that this also happens in maize seedlings, through the promotion of the G1− S1 phase transition during the cell cycle. 40 These data indicate a phenomenon similar to that documented for animal cells in response to insulin. 3,46 To determine the endogenous growth factor content of these calli, Western blot analysis were performed using an antibody raised against human insulin that was previously demonstrated to recognize the purified ZmIGF.…”
Section: ■ Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Previous results from our research group have already proven that cell division in calli tissues occurs by stimulation with ZmIGF or insulin, 39 and recent evidence also showed that this also happens in maize seedlings, through the promotion of the G1− S1 phase transition during the cell cycle. 40 These data indicate a phenomenon similar to that documented for animal cells in response to insulin. 3,46 To determine the endogenous growth factor content of these calli, Western blot analysis were performed using an antibody raised against human insulin that was previously demonstrated to recognize the purified ZmIGF.…”
Section: ■ Resultssupporting
confidence: 78%
“…This phenomenon has also been demonstrated on insulin-stimulated maize seedlings, 37 as well as in ribosome biogenesis, observed in the same system. 38 Furthermore, insulin and ZmIGF have previously been shown to increase the rate of maize seedling and callus mitosis, 16,39 processes that were recently confirmed to occur by the activation of S phase genes promoting cell cycle progression in maize 40 and Arabidopsis 15 tissues. The identity of IGF-like growth factors in plants is scarce; even though few reports indicate their existence on leguminose, 30,31 maize, 16,36 potato, 34 and Arabidopsis, 35 although most of them have not been shown to regulate plant growth through the TOR pathway.…”
Section: ■ Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5A). This is in accordance with previous reports for maize indicating that re-initiation of cell division occurs around 18 h of imbibition [56] and it should be accompanied by intense protein synthesis activity. Hence, new ribosome biogenesis should also occur at high rate.…”
Section: Effect Of Insulin On the De Novo Synthesis Of Ribosomal Prot...supporting
confidence: 94%
“…Cells in maize dessicated seeds during maturation are arrested in the transition G1/S and when seeds are imbibed the cell cycle is reactivated [57]. Also, our research group has previously shown that insulin stimulates the aforementioned transition and reactivates the cell cycle after 15 h of imbibition in presence of this effector [56]; therefore, we decided to look for the presence of the rRNA precursors in maize seeds imbibed in presence of insulin for periods shorter than 15 h (3 and 6 h) by using labeled probes against the mature rRNA and against the pre-rRNA (including ITS1, 5.8S and ITS2) according to the methodology described by Cevallos et al [58]. Results show that insulin induces rRNA precursors as well as 5.8 rRNA accumulation in maize seeds imbibed for 3 and 6 h (Fig.…”
Section: Discussionmentioning
confidence: 90%